Increasing Appropriate Composting in High-Traffic University Settings - Szczucinski, David (Behav Anal Pract, 2019)
Composting systems are poised to make a significant impact on waste-management strategies and greatly contribute to global sustainability efforts. However, risk of contamination by potentially detrimental compounds must be overcome before these systems can be widely adopted. Behavior analytic approaches to waste disposal adherence have consisted of antecedent and consequence strategies; many such strategies require continual oversight and significant investment of resources to maintain effectiveness. This project describes a field study that investigated a purely antecedent-based approach to nudge proper organic recycling on a university campus. Using a multiple-baseline design across dining sites, we demonstrate the efficacy of enhanced compost bins (i.e., green colored bins with a hinged door and an accompanying placard indicating site-specific materials that can and cannot be composted) to reduce product contamination by inorganic or unsuitable organic refuse. Implications for future research and suggestions for university implementation are discussed.